Developmental origins for semilunar valve stenosis identified in mice harboring congenital heart disease-associated GATA4 mutation - Stephanie LaHaye; Uddalak Majumdar; Jun Yasuhara; Sara N. Koenig; Adrianna Matos-Nieves; Rahul Kumar; Vidu Garg (The Company of Biologists, 2019)
Congenital heart defects affect ∼2% of live births and often involve malformations of the semilunar (aortic and pulmonic) valves. We previously reported a highly penetrant GATA4 p.Gly296Ser mutation in familial, congenital atrial septal defects and pulmonic valve stenosis and showed that mice harboring the orthologous G295S disease-causing mutation display not only atrial septal defects, but also semilunar valve stenosis. Here, we aimed to characterize the role of Gata4 in semilunar valve development and stenosis using the Gata4G295Ski/wt mouse model. GATA4 is highly expressed in developing valve endothelial and interstitial cells. Echocardiographic examination of Gata4G295Ski/wt mice at 2 months and 1 year of age identified functional semilunar valve stenosis predominantly affecting the aortic valve with distal leaflet thickening and severe extracellular matrix (ECM) disorganization. Examination of the aortic valve at earlier postnatal timepoints demonstrated similar ECM abnormalities consistent with congenital disease. Analysis at embryonic timepoints showed a reduction in aortic valve cushion volume at embryonic day (E)13.5, predominantly affecting the non-coronary cusp (NCC). Although total cusp volume recovered by E15.5, the NCC cusp remained statistically smaller. As endothelial to mesenchymal transition (EMT)-derived cells contribute significantly to the NCC, we performed proximal outflow tract cushion explant assays and found EMT deficits in Gata4G295Ski/wt embryos along with deficits in cell proliferation. RNA-seq analysis of E15.5 outflow tracts of mutant embryos suggested a disease state and identified changes in genes involved in ECM and cell migration as well as dysregulation of Wnt signaling. By utilizing a mouse model harboring a human disease-causing mutation, we demonstrate a novel role for GATA4 in congenital semilunar valve stenosis. This article has an associated First Person interview with the joint first authors of the paper.